Assessment of achievement in problem-solving skills in a General Chemistry course - Patricia Morales Bueno (OmniaScience, 2014)
This article reports the development and validation study of tests to assess achievements at three levels of knowledge structure, following the model proposed by Sugrue to measure problem-solving skills. This model is particularly consistent with the theoretical constructs underlying problem-based learning (PBL) methodology. The tests were constructed for a General Chemistry course in a curriculum of engineering, which implements PBL methodology at a Peruvian university. The content validation of the tests was performed, as well as a pilot implementation with Peruvian students of first year enginnering. The results obtained in omissions percentage, difficulty degree, items response pattern and the point biserial coefficient (rpb), let us to conclude that these are appropiate tools for assessing these skills, so constitute a significant contribution to future research in this line.